2018
DOI: 10.1002/hbm.24233
|View full text |Cite
|
Sign up to set email alerts
|

Regional structural hypo‐ and hyperconnectivity of frontal–striatal and frontal–thalamic pathways in behavioral variant frontotemporal dementia

Abstract: Behavioral variant frontotemporal dementia (bvFTD) has been predominantly considered as a frontotemporal cortical disease, with limited direct investigation of frontal-subcortical connections. We aim to characterize the grey and white matter components of frontal-thalamic and frontal-striatal circuits in bvFTD. Twenty-four patients with bvFTD and 24 healthy controls underwent morphological and diffusion imaging. Subcortical structures were manually segmented according to published protocols. Probabilistic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 67 publications
7
28
0
Order By: Relevance
“…In parallel, within-module degree and participation coefficient in many striatum ROIs were altered (both higher and lower) in bvFTD when compared to HC (degree) and AD (participation coefficient). Compared to controls, patients with bvFTD have previously shown reduced functional connectivity in frontoinsular and basal ganglia networks [ 43 ]; volumetric changes in striatal and thalamic regions were also reported in bvFTD [ 59 ] and other FTD syndromes (thalamus [ 14 ];). The cortico-striatal-thalamic connections are essential to many fundamental cognitive processes such as cognitive control [ 54 ], emotion regulation [ 64 , 83 ], and reward-decision making [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, within-module degree and participation coefficient in many striatum ROIs were altered (both higher and lower) in bvFTD when compared to HC (degree) and AD (participation coefficient). Compared to controls, patients with bvFTD have previously shown reduced functional connectivity in frontoinsular and basal ganglia networks [ 43 ]; volumetric changes in striatal and thalamic regions were also reported in bvFTD [ 59 ] and other FTD syndromes (thalamus [ 14 ];). The cortico-striatal-thalamic connections are essential to many fundamental cognitive processes such as cognitive control [ 54 ], emotion regulation [ 64 , 83 ], and reward-decision making [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to show alterations of subcortical structures in both nodal and modular organization in bvFTD. While more replications are needed to ascertain the direction and functional implications of the FC and organizational changes in the striatum and thalamus, finding from Jakabek and colleagues [ 59 ] suggested that these relationships might be dependent on regional structural connectivity. Specifically, their bvFTD patients had overall lower subcortical gray matter volume than HC, but striatal and thalamic regions with white matter connection to the medial prefrontal cortex, unexpectedly had significantly larger volume, possibly representing compensatory or maladaptive network remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of abnormalities in the TDP-43 G298S mice, as detected at this stage of the disease progression, shows closer similarities with FTD patients rather than with ALS patients: whereas in the latter the involvement of motor cortex and CST is prominent early in disease progression [5, 17], in the former a subset of patients with intact CST can be identified [18]. FTD patients also show DTI changes in frontal callosal fibers [8] and in the thalamus [15]. It is important to note that the dissociation between grip-strength abnormalities, FA changes and normal CST metrics may be limited to the stage of progression under study (about 450 days of age); whether CST abnormalities might appear at later stages in the TDP-43 G298S mice, with the progression of the involvement of neuronal subpopulations, remains object of active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have demonstrated that atrophy of these frontal and anterior temporal regions is related to the behavioral symptoms observed in bvFTD, including apathy, disinhibition, loss of empathy, and aggression [40][41][42][43][44][45][46][47][48][49][50] . Atrophy of subcortical structures, such as caudate, putamen, globus pallidus, thalamus and nucleus accumbens, are also observed, reflecting dysfunction of cortico-striato-thalamic circuits 51 which have also been associated with behavioral abnormalities in bvFTD [52][53][54][55][56][57][58][59][60][61] . Neurodegeneration in bvFTD is progressive, with decline in brain volume observed over time.…”
Section: Imaging In the Clinical Syndromes Of Ftd Behavioral Variant Ftdmentioning
confidence: 99%
“…Degeneration of these tracts is associated with behavioral severity in bvFTD 45,96 . Degeneration is also observed in fronto-striatal and fronto-thalamic pathways 51 . Less severe degeneration is also observed in tracts that connect into posterior regions of the brain, including the posterior cingulate and posterior aspects of the superior longitudinal fasciculus.…”
Section: Imaging In the Clinical Syndromes Of Ftd Behavioral Variant Ftdmentioning
confidence: 99%